A Vascular Malformation in the Carotid Sheath at the Carotid Bifurcation Mimicking Carotid Body Tumor. (February 2020) - Gao, Xixiang; Li, Yang; Meng, Liang; Tong, Zhu; Guo, Lianrui; Zhang, Jian; Gu, Yongquan
Background: The carotid sheath contains clinically important and vital anatomical neurogenic, vascular, and lymphatic structures that allow for a great variety of lesions. Vascular anomalies found in the carotid sheath are rarely reported and may be easily misdiagnosed as arterial aneurysms, neurogenic tumors, paragangliomas, or lymphatic masses. Method: We present a 60-year-old woman with a vascular malformation arising within the carotid sheath at the right carotid bifurcation, which mimics carotid body tumor. Result: The mass was excised successfully with an uneventful postoperative course, and histological analysis suggested a vascular malformation with thin-walled blood vessels, lined by endothelial cells and separated by fibrous tissue. The patient was in good clinical condition without signs of relapse of the mass at 6-month follow-up. Conclusion: Vascular malformation is a rare but existing possibility of pathology in the carotid sheath, which can be effectively removed by meticulous surgery.